Do preoperative oral antibiotics increase Clostridium difficile infection rates? An analysis of 13 959 colectomy patients. (3rd June 2018) - Parthasarathy, M.; Bowers, D.; Groot‐Wassink, T.
Abstract: Aim: The aim of this study was to determine whether or not preoperative oral antibiotic preparation (POAP) increases the rate of Clostridium difficile colitis (CDC) in patients undergoing colectomy. Method: In 2015, data for colectomies had been collected prospectively and recorded in the targeted colectomy option of the American College of Surgeons National Surgical Quality Improvement Program (ACS NSQIP). This was available for retrospective analysis. Data available for analysis included elective and emergency status, POAP, surgical approach, primary anastomosis and CDC status. The effect of POAP on CDC was analysed and risk adjusted for 14 separate preoperative variables. Results: In all, 13 959 adult patients underwent a colectomy in 2015 (POAP group 5311 and non‐ POAP group 8648). The overall rate of CDC in colectomy patients was 1.6% (227/13 959). On univariate analysis, CDC was significantly less common in the POAP group than in the non‐POAP group (1.2% vs 1.9%, P = 0.003). Univariate analysis of a further 41 preoperative variables revealed 14 to be associated with CDC. However, after risk adjustment with these 14 variables, POAP lost its statistical significance (adjusted OR 0.902, 95% CI 0.584–1.486, P = 0.685). Only patients with pre‐existing systemic inflammatory response syndrome appeared to be at increased risk of CDC (adjusted OR 2.154, 95% CI 1.139–4.074, P = 0.018). Conclusion: At the very least this study suggests it is safe to use POAP in colectomy patients without increasing the rate of CDC unless they have pre‐existing systemic inflammatory response syndrome.